Strategija razvoja mestnih gozdov Ljubljane - Simončič, Tina (Gozdarski vestnik, 2021)
The City of Ljubljana Urban Forest Development Strategy defines the vision and long-term priorities of the Ljubljana urban forests development. The strategy represents the basis for managing urban forests which significantly contribute to ensuring a healthy living environment for the citizens and visitors of the city. The strategy expresses/considers the local community%s interest in forests in the city and its direct surroundings and contributes to responsible forest management planning for the needs of the community. On the initiative of the Municipality of Ljubljana, the Strategy was prepared in the frame of URBforDAN project of the INTERREG framework for the area of the Ljubljana urban forests, that is, of all those who are defined as forests with extremely emphasized social functions according to the municipality spatial plan. The strategy intends to motivate diverse institutions, non-governmental organizations, and individuals for a more active participation in co-decision on the Ljubljana urban forests development, to build up the awareness of the significance of these forests, and to improve bases for managing the forests which boost social and ecological functions. The article presents the main characteristics of the City of Ljubljana Urban Forest Development Strategy, including goals and guidelines. The strategy sets frameworks for the system of organizational, financial, and other measures to improve the harmonization of public interests in urban forest space which is predominantly privately owned. It also highlights the importance of cooperation with private owners for ensuring social functions in urban forests.
Keywords: gospodarjenje z gozdovi; Ljubljana; mestni gozdovi; urbano gospodarstvo